2018
DOI: 10.3390/molecules23082062
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-QTOF/MS-Based Metabolomics Applied for the Quality Evaluation of Four Processed Panax ginseng Products

Abstract: In the food industry and herbal markets, it is critical to control the quality of processed Panax ginseng products. In this study, ultra-performance liquid chromatography coupled to quadrupole time of flight mass spectrometry (UPLC-QTOF/MS)-based metabolomics was applied for the quality evaluation of white ginseng (WG), tae-geuk ginseng (TG), red ginseng (RG), and black ginseng (BG). Diverse metabolites including ginsenosides were profiled by UPLC-QTOF/MS, and the datasets of WG, TG, RG, and BG were then subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…In the study, Table showed that a total of 20 ginsenosides were identified through comparing the m/z values, fragment ions, and retention times with those of the reference compounds (Lee, Park, Lee, Jayakodi, Kim, Koo, et al, ; Qi et al, ). Previous studies have reported that ion sensitivities of saponins were high in the negative ion mode (Wang et al, ; Lee et al, ). In the negative ion mode MS spectra, most of the ginsenosides exhibited deprotonated ions [M‐H] − or formic acid adduct ions [M + HCOO] − .…”
Section: Resultsmentioning
confidence: 97%
“…In the study, Table showed that a total of 20 ginsenosides were identified through comparing the m/z values, fragment ions, and retention times with those of the reference compounds (Lee, Park, Lee, Jayakodi, Kim, Koo, et al, ; Qi et al, ). Previous studies have reported that ion sensitivities of saponins were high in the negative ion mode (Wang et al, ; Lee et al, ). In the negative ion mode MS spectra, most of the ginsenosides exhibited deprotonated ions [M‐H] − or formic acid adduct ions [M + HCOO] − .…”
Section: Resultsmentioning
confidence: 97%
“…Instead of processing by air-drying and heating for short periods, red ginseng is prepared by steaming fresh ginseng at 95–100 °C for 2–3 h before drying. The color of the ginseng changes from white/yellow to red after steaming [ 71 , 72 ]. Red ginseng is reportedly more pharmacologically active than WG and is commonly consumed around the world.…”
Section: Variations In Ginsenoside Compositions Due To Different Pmentioning
confidence: 99%
“…A previous study on ginsenosides of processed ginseng products was conducted using UPLC-QTOF/MS-based metabolomics. Malonyl-ginsenoside Rb1, Rb2, Rc, ginsenoside Re, and Rg1 are the major constituents of WG, ginsenoside Rb2, Rc, Rd, Re, and Rg1 are the major constituents of TG, ginsenoside Rb1, Rb2, Rc, Rd, Re, and Rg1 are the major constituents of RG, and ginsenoside Rd, Rk1, Rg5, and Rg3 are the major constituents of BG [6,7]. Depending on the processing method, the amount of ginsenosides may be increased or decreased by chemical transformation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, malonyl-ginsenosides are demalonylated to neutral ginsenosides during processing. After steaming, the amount of ginsenoside Rd, Rg3, Rk1, and Rg5 is increased, and the amount of ginsenoside Rg3, Rk1, and Rg5 is considerably elevated by increasing the steam cycles [6]. Although many studies on the changes of ginsenosides due to processing have been previously conducted, little research has been conducted on primary metabolites, which constitute the majority of processed ginseng.…”
Section: Introductionmentioning
confidence: 99%